Identifying and Prioritizing of Factors Influencing the Entry of Medical Centers on the Medical Tourism Market in Iran - Mohammad Reza Dehghani; Najmeh Baghian; Mohammad Hossien Dehghani (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: Medical tourism is a fast-growing industry that has provided special opportunities for international organizations to achieve a competitive advantage. This research has been conducted to recognize and prioritize the factors affecting the admission of medical centers into the medical tourism market in Iran. Methods: The combined study was conducted in two qualitative stages and hierarchical analysis in governmental and non-governmental centers related to medical tourism on 15 experts and specialists in the qualitative stage and 25 people in a quantitative stage. The interview guide was used to collect data in the qualitative stage and the pairwise comparison questionnaire was used in the hierarchical analysis stage. Qualitative phase results were analyzed by conceptual framework method and quantitative phase results were analyzed by AHP method applying 11 Expert Choice software. Results: 41 sub-themes were identified in the qualitative stage, which were categorized into six groups: service quality, infrastructure, human, information, economic and political. The highest weight or priority was related to the diversity and quality of services and the lowest weight or priority was associated with the field of information and marketing among the six factors based on the Analytical Hierarchy process (AHP) method. Conclusion: The most significant factor for medical centers to join the health tourism market is to focus on the quality of provided services based on the results. It is recommended that medical centers provide all services from the time of admission to follow-up after discharge in the context of intelligent and web-based systems in order to strengthen the quality of services, in addition to standardize departments and treatment processes according to international standards.